Cell surface downregulation of NK cell ligands by patient-derived HIV-1 Vpu and Nef alleles - Galaski, Johanna; Tibroni, Nadine; Pujol, Franc̦ois; Müller, Birthe; Fackler, Oliver Till (Journal of acquired immune deficiency syndromes, 2016)
Objective: HIV-1 Vpu and Nef proteins downregulate cell surface levels of natural killer (NK) cell ligands but functional consequences of individual downregulation events are unclear. We tested how well-conserved NK cell ligand downregulation is among Vpu and Nef variants isolated from chronic HIV patients. - Methods: Proviral vpu and nef sequences were amplified from 27 chronic HIV patients, subcloned, and tested for their ability to downregulate cell surface receptors. - Results: Cell surface downregulation of CD4, CD317/tetherin, and major histocompatibility complex class 1 that exert biological functions other than NK cell activation were well conserved among patient-derived Vpu and Nef variants. Among NK cell ligands, NK-T-B-antigen, poliovirus receptor, and UL16-binding protein were identified as main targets for Vpu and Nef, the downregulation of which by at least 1 viral protein was highly conserved. NK cell ligands displayed specific sensitivity to Vpu (NK-T-B-antigen) or Nef (poliovirus receptor), and downregulation of cell surface UL16-binding protein was identified as a novel and highly conserved activity of HIV-1 Vpu but not Nef. - Conclusions: The conservation of downregulation of major NK cell ligands by either HIV-1 Vpu or Nef suggests an important pathophysiological role of this activity, which may impact the acute but not the chronic phase of HIV infection.